67.7k views
5 votes
PLEASE HELP ME . - Simplify the expression (x5)1/9. a - 5x^9 . b - 9x^5 . c - x^ 5/9 . d - x^9/5

User Kkpattern
by
5.5k points

1 Answer

5 votes

Answer:

Option C)
x^{(5)/(9)} is correct

Therefore
(x^5)^{(1)/(9)}=x^{(5)/(9)}

Explanation:

Given expression is

To simplify the given expression :


(x^5)^{(1)/(9)}


=(x)^{5* (1)/(9)} ( using the property
(a^m)^n=a^(mn) )


=x^{(5)/(9)}

Therefore
(x^5)^{(1)/(9)}=x^{(5)/(9)}

Therefore option C)
x^{(5)/(9)} is correct

Therefore the simplified expression is
x^{(5)/(9)}

User Ryan Plant
by
5.3k points